Template metaprogramming with C++ : learn everything about C++ templates and unlock the power of template metaprogramming - Bancila, Marius (Packt Publishing, Limited, 2022)
Understand how to use modern C++ templates for writing maintainable, robust, and fast software Key Features Grasp the fundamentals of and learn to write effective C++ templates Get up to speed with the latest C++20 template features such as constraints and concepts Explore different patterns and idioms to integrate templates in your program design Book Description Learn how the metaprogramming technique enables you to create data structures and functions that allow computation to happen at compile time. With this book, you'll realize how templates help you avoid writing duplicate code and are key to creating generic libraries, such as the standard library or Boost, that can be used in a multitude of programs. The introductory chapters of this book will give you insights into the fundamentals of templates and metaprogramming. You'll then move on to practice writing complex templates and exploring advanced concepts such as template recursion, template argument deduction, forwarding references, type traits, and conditional compilation. Along the way, you'll learn how to write variadic templates and how to provide requirements to the template arguments with C++20 constraints and concepts. Finally, you'll apply your knowledge of C++ metaprogramming templates to implement various metaprogramming patterns and techniques. By the end of this book, you'll have learned how to write effective templates and implement metaprogramming in your everyday programming journey. What you will learn Understand the syntax for all types of templates Discover how specialization and instantiation works Get to grips with template argument deduction and forwarding references Write variadic templates with ease Become familiar with type traits and conditional compilation Restrict template arguments in C++20 with constraints and concepts Implement patterns such as CRTP, mixins, and tag dispatching Who this book is for This book is for beginner-to-intermediate C++ developers who want to learn about template metaprogramming as well as advanced C++ developers looking to get up to speed with the new C++20 features related to templates and the the various idioms and patterns. Basic C++ coding experience is necessary to get started with this book.